Surface creasing-induced micropatterned gelMA using heating-hydration fabrication for effective vascularization - Kasetsiriku, Surasak (2022)
Surface modification is used to modify the biomaterials for the regulation of cell culture using different approaches, such as chemical graft and mechanical treatment. However, those conventional methodologies often require precise fabrication in a high resolution involving either high cost or laborious steps to remove chemical residues that are toxic to the cells.